Lifestyle and fertility-specific quality of life affect reproductive outcomes in couples undergoing in vitro fertilization - Urata, Yoko; Harada, Miyuki; Komiya, Shinnosuke; Akiyama, Ikumi; Tuchida, Chihiro; Nakaoka, Yoshiharu; Fukuda, Aisaku; Morimoto, Yoshiharu; Kawahara, Takuya; Ishikawa, Yusuke; Osuga, Yutaka (Frontiers in Endocrinology, 2024)
A Mediterranean dietary pattern, sleeping habits, physical activity, and lifestyle appear to affect reproductive health. There are few reports about whether fertility-specific quality of life (QOL) is linked to infertility treatment outcomes. The aim of this study is to investigate when lifestyle factors and fertility-specific QOL are comprehensively considered, which factors influence assisted reproductive technology (ART) outcomes. This prospective cohort includes 291 women undergoing a first ART treatment and was designed to evaluate the influence of diet, physical activity, sleeping pattern, computer use duration, and fertility-specific quality of life tool (FertiQoL) score on ART treatment outcomes using a questionnaire. The good-quality blastocyst rate per oocyte retrieval tended to be negatively affected by frequent fish consumption. Gestational sac (GS) detection was positively and significantly affected by frequent olive oil intake and longer computer use, and tended to be positively affected by a higher FertiQoL Total scaled treatment score. A positive pregnancy test was positively and significantly affected by longer computer use, and tended to be negatively affected by a smoking partner. Olive oil may be an important factor in dietary habits. Fertilityspecific QOL and smoking cessation guidance for partners are important for infertile couples.